ETUDE DE LA GAMETOGENESE CHEZ LE MOLLUSQUE BIVALVE CARDIUM COSTATUM (LINNE, 1758) DE LA ZONE ECONOMIQUE EXCLUSIVE DE LA COTE D’IVOIRE - Fulgence, Kouato; Mamadou, Karamoko; Atcho, Otchoumou; Franck Didier, Adou Coffi (European Scientific Journal, ESJ, 2015)
Cardium costatum (Linne, 1758) is a marine mollusc bivalve fishing in the exclusive economic zone (EEZ) of Côte d’Ivoire and unload in Abidjan fishing port mainly by trawlers. It is the species of the most common and abundant in bivalve landings. In order to update the data for its sustainable management and initiate shellfish farming, the gametogenesis was studied during two year period (November 2012 to October 2014). The study conducted on basis of histological observations on the male and female gonads. The description stage for male and female shows gonadic follicles and tubules contain only undifferentiated germinal cells (stage 1). Stage 2 is marked by early developing where follicles and tubules contain cells in their initial stage of mitotic development. Stage 3 is marked by oogenesis or spermatogenesis, which, according to sex, is active from the periphery to the lumen of follicles and tubules. Oocytes are mostly stalked while spermatozoa observed in the lumen. At maturity (stage 4), the majority of oocytes are no longer stalked and invade the lumen of follicles. Spermatozoa in turn are more abundant in the tubule lumen. Stage 5 is marked by the laying and the emission of gametes. Cardium costatum is gonochoric species but Hermaphrodites cases were reported during this study.